Orientasi Nilai, Pengetahuan Ekologikal, Afek Ekologikal Meningkatkan Niat Beli Produk Kosmetik Ramah Lingkungan - Masruroh; Ardie Kusumawan (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The purpose of this research is examining the influence of value orientation, ecological knowledge and ecological effect on the purchase intention to the green cosmetic product. The instrument of this thesis is Linier Regression Analysis. The research design applies confirmatory study that uses survey approach. The primary data is obtained from cross section method taken from 180 respondents. The respondents are female is above 17 years old who knows and/or uses green cosmetic product. The result of this research shows that value orientation does not influence positively to the ecological knowledge. However, the value orientation influence positively to the ecological effect. The ecological knowledge impact positively to the ecological affect. The ecological knowledge and ecological effect impact positively to the purchase intention. This thesis gives an important contribution to the next research to pay attention to the factors of purchase intention to the green cosmetic product.